Sex Differences in the Use of Oral Anticoagulants for Atrial Fibrillation: A Report From the National Cardiovascular Data Registry (NCDR®) PINNACLE Registry. Issue 7 (19th July 2017) - Thompson, Lauren E.; Maddox, Thomas M.; Lei, Lanyu; Grunwald, Gary K.; Bradley, Steven M.; Peterson, Pamela N.; Masoudi, Frederick A.; Turchin, Alexander; Song, Yang; Doros, Gheorghe; Davis, Melinda B.; Daugherty, Stacie L.
Abstract : Background: Despite higher thromboembolism risk, women with atrial fibrillation have lower oral anticoagulation (OAC) use compared to men. The influence of the CHA2 DS2 ‐VASc score or the introduction of non–vitamin K OACs on this relationship is not known. Methods and Results: Using the PINNACLE National Cardiovascular Data Registry from 2008 to 2014, we compared the association of sex with OAC use (warfarin or non–vitamin K OACs) overall and by CHA2 DS2 ‐VASc score and examined temporal trends in OAC use by sex. Multivariable regression models assessed the association between sex and OAC use in those with CHA2 DS2 ‐VASc scores ≥2. Temporal analyses assessed changes in OAC use by sex over time. Of the 691 906 atrial fibrillation patients, 48.5% were women. Women were significantly less likely than men to use any OAC overall (56.7% versus 61.3%; P <0.001) and at all levels of CHA2 DS2 ‐VASc score (adjusted risk ratio 9% to 33% lower, all P <0.001). Compared to other thromboembolic risk factors, female sex was associated with lower use of OAC (risk ratio 0.90, 95%CI 0.90‐0.91). Over time, non–vitamin K OAC use increased at a slightly higher rate in women (56.2% increase per year, 95%CI 54.6% to 57.9%) compared to men (53.6% increase per year, 95%CI 52.0% to 55.2%), yet women remained less likely to receive any OAC at all time points ( P <0.001). Conclusions: Among patients with atrial fibrillation, women were significantly less likely to receive OAC at all levels of the CHA2 DS2 ‐VASc score. Despite increasing non–vitamin K OAC use, women had persistently lower rates of OAC use compared to men over time.